.2(-16+-6)=.3d*-16+5-3+.1d

Simple and best practice solution for .2(-16+-6)=.3d*-16+5-3+.1d equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for .2(-16+-6)=.3d*-16+5-3+.1d equation:


Simplifying
0.2(-16 + -6) = 0.3d * -16 + 5 + -3 + 0.1d

Combine like terms: -16 + -6 = -22
0.2(-22) = 0.3d * -16 + 5 + -3 + 0.1d

Multiply 0.2 * -22
-4.4 = 0.3d * -16 + 5 + -3 + 0.1d

Reorder the terms for easier multiplication:
-4.4 = 0.3 * -16d + 5 + -3 + 0.1d

Multiply 0.3 * -16
-4.4 = -4.8d + 5 + -3 + 0.1d

Reorder the terms:
-4.4 = 5 + -3 + -4.8d + 0.1d

Combine like terms: 5 + -3 = 2
-4.4 = 2 + -4.8d + 0.1d

Combine like terms: -4.8d + 0.1d = -4.7d
-4.4 = 2 + -4.7d

Solving
-4.4 = 2 + -4.7d

Solving for variable 'd'.

Move all terms containing d to the left, all other terms to the right.

Add '4.7d' to each side of the equation.
-4.4 + 4.7d = 2 + -4.7d + 4.7d

Combine like terms: -4.7d + 4.7d = 0.0
-4.4 + 4.7d = 2 + 0.0
-4.4 + 4.7d = 2

Add '4.4' to each side of the equation.
-4.4 + 4.4 + 4.7d = 2 + 4.4

Combine like terms: -4.4 + 4.4 = 0.0
0.0 + 4.7d = 2 + 4.4
4.7d = 2 + 4.4

Combine like terms: 2 + 4.4 = 6.4
4.7d = 6.4

Divide each side by '4.7'.
d = 1.361702128

Simplifying
d = 1.361702128

See similar equations:

| x/13+2=5 | | 4x-14=86 | | 7j+11p=34.99 | | 9x+15=-3 | | X^2+11x+10=o | | x/9-8=3 | | 0.029x+4=0.034x | | 0.2x-1=6 | | 3x-6(x+6)=-66 | | -3(6+7)x=171 | | 5x^2+42=2x^2+117 | | 6x^2+9x-8=0 | | 7(1x+3)=105 | | A+B+15=45 | | 7x+2(4x+8)=4 | | 7+10n=37 | | -8+6(3g+6)= | | 180=y-4 | | -3x-8y+20y=5x+19 | | 4x^2-2x-120=0 | | 11x-4=11+2 | | 4(-5x-6)=-4 | | x/5+17=20 | | 2(7-4x)=-74 | | 9y^2+27y+14= | | 7(-7x+8)=-483 | | 12x+23=71 | | x^3=167 | | 17.00+5.50h=11.00+6.75h | | 98=7x-7 | | 4y-5y=81 | | 10+4c=5(c-6)+33 |

Equations solver categories